2016
DOI: 10.14260/jemds/2016/883
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Patients With Peptic Ulcer Perforation With Respect to Aetiology and Factors Affecting Outcome of Management

Abstract: BACKGROUNDPerforation peritonitis is one of the commonest surgical emergency encountered by surgeons. The aim of the study is to provide an overview of aetiological factors causing peptic ulcer perforation and the factors affecting the outcome of management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…In our study, the majority of study participants reported history of alcohol consumption (54.3%) and previous NSAID use (71.6%) but only 32.1% smoked cigarette. These factors have been associated with peptic ulcer perforation in previous studies [ 18 ].…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the majority of study participants reported history of alcohol consumption (54.3%) and previous NSAID use (71.6%) but only 32.1% smoked cigarette. These factors have been associated with peptic ulcer perforation in previous studies [ 18 ].…”
Section: Discussionmentioning
confidence: 97%